Strategic framework for underutilized plant species: With special reference to Asia and the Pacific, and to Sub-Saharan Africa - Global Facilitation Unit for Underutilized Species (2006)
This framework is the product of a global electronic consultation and two regional workshops earlier in 2006 organised by ICUC, GFU and IPGRI. It reviews current activities, provides examples of success and emphasizes the need to improve resource mobilization in support of underutilized plant species research and development, including urgent work to collect baseline information and formulate meaningful indicators to guide future action.